(3TQM Ydi ef dG jMVQg Gdabjgs - (3GdMGQKj GdYGedj GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s
(3ChdgG (B:s
(3CHgi NHQ jHJOC Hg GdcdGe, hCMSf MOjK jaJM Hg GdeQGe(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG bhdg(B: ...(3hGYJQV Ydjg HYV GdCUMGH HCf gPG GdMOjK bGUQ Yf EaGOI eG GOYGg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B102s
(3GdPQjYI(B:(3L(B6(3,U(B163(3,Qbe(B1260s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis